1991
DOI: 10.1152/jappl.1991.70.1.405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bronchial arterial PO2 on pulmonary vascular resistance

Abstract: In six anesthetized and mechanically ventilated adult sheep, the bronchial artery was perfused with blood from an oxygenator-pump circuit. When the lungs were ventilated with 100% O2 and the bronchial O2 tension (PbrO2) was approximately 600 Torr, the mean of the pulmonary vascular resistances (PVR) measured at the beginning (3.32 +/- 0.29 units) and end (3.17 +/- 0.13 units) of the experiment was 3.24 +/- 0.20 units. When the PbrO2 was changed to 58 +/- 1 Torr, the PVR (2.99 +/- 0.14 units) did not change sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Most investigators believe this omission is reasonable, since bronchial blood flow is so much smaller than pulmonary blood flow. Nevertheless, when the bronchial circulation of sheep was perfused at a pressure 40 mmHg higher than mean systemic arterial pressure (and thus at higher bronchial blood flow), decreases in bronchial arterial PO 2 caused modest HPV during ventilation with air, but not during ventilation with 100% O 2 (1194). Whether P a O 2 is a significant determinant of P s O 2 in intact animals remains unclear.…”
Section: Measurement Of Stimulus and Responsementioning
confidence: 99%
“…Most investigators believe this omission is reasonable, since bronchial blood flow is so much smaller than pulmonary blood flow. Nevertheless, when the bronchial circulation of sheep was perfused at a pressure 40 mmHg higher than mean systemic arterial pressure (and thus at higher bronchial blood flow), decreases in bronchial arterial PO 2 caused modest HPV during ventilation with air, but not during ventilation with 100% O 2 (1194). Whether P a O 2 is a significant determinant of P s O 2 in intact animals remains unclear.…”
Section: Measurement Of Stimulus and Responsementioning
confidence: 99%
“…First, the absolute lung volume-FRC-is related to PVR through direct static effects on vascular compression. Studies in ex vivo lungs suggested that the relationship of lung volume with PVR followed a "U" shaped curve, with the PVR nadir at FRC (47,48). Second, data from in vivo isolated lung lobes suggest that the effects of nous O 2 tension, rather than lung volume per se (49).…”
Section: Atelectasis and Right Ventricular Dysfunctionmentioning
confidence: 99%
“…Possibly, the arterial oxygenation of the bronchial circulation may add to the response too (Marshall et al . ). The degree of HPV reflects the severity of the hypoxic stimulus until very low oxygen tensions are reached and the HPV response may be blunted at inspiratory oxygen fractions <0.10 (De Canniere et al .…”
mentioning
confidence: 97%